Investigation of Magneto-phonon Resonance in Graphene Monolayers - Hoi, Bui Dinh; Phuong, Le Thi Thu; Duyen, Tran Thi My; Lam, Vo Thanh (VNU Journal of Science: Mathematics - Physics, 2017)
In this work, utilising the linear response theory we calculate the magneto conductivity (MC) in graphene monolayers, subjected to a static perpendicular magnetic field. The interaction of Dirac fermions with optical phonon via deformation potential is taken into account at high temperature. The dependence of the MC on the magnetic field shows resonant peaks that describe transitions of electrons between Landau levels via the resonant scattering with optical phonons. The effect of temperature on the MC is also obtained and discussed.